2016
DOI: 10.1002/2016ja023258
|View full text |Cite
|
Sign up to set email alerts
|

A stable auroral red (SAR) arc with multiple emission features

Abstract: Stable auroral red (SAR) arcs offer subvisible evidence for storm time linkages between the inner magnetosphere and the midlatitude ionosphere. A SAR arc's defining characteristics are horizon‐to‐horizon east‐west extent, a few degrees of latitude in meridional extent, emission only at the oxygen 6300 Å line, and minimal brightness changes during a night—effects readily provided by steady heat conduction from the ring current‐plasmapause interaction region. Here we describe a typical SAR arc (brightness ~300 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 36 publications
2
15
0
1
Order By: Relevance
“…We simply hypothesize that the red lines were a standard stable auroral red (SAR) arc, and that the other colors reflect "white pillars" due to field-aligned currents carried by precipitating electrons. In a similar recent example, Mendillo et al (2016) demonstrated a detailed analysis of the SAR arc, where several superimposed patches of green line emission were found during a magnetic storm. Enhancements in total electron content and radio wave scintillations at the patches support electron precipitation from the plasma sheet (Aarons, 1987).…”
Section: Possible Mechanisms Of Fan-shaped Auroramentioning
confidence: 88%
“…We simply hypothesize that the red lines were a standard stable auroral red (SAR) arc, and that the other colors reflect "white pillars" due to field-aligned currents carried by precipitating electrons. In a similar recent example, Mendillo et al (2016) demonstrated a detailed analysis of the SAR arc, where several superimposed patches of green line emission were found during a magnetic storm. Enhancements in total electron content and radio wave scintillations at the patches support electron precipitation from the plasma sheet (Aarons, 1987).…”
Section: Possible Mechanisms Of Fan-shaped Auroramentioning
confidence: 88%
“…This is in contrast to the rarer case of a SAR arc with structured patches of emission. Mendillo, Finan, et al (2016) showed unusual SAR arcs that included regions of enhanced 630.0-and 557.7-nm emission that did exhibit GPS phase fluctuations. These resulted from low energetic particle precipitation due to inward motion of ring current particles (Shiokawa et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…They showed not only very long lasting SAR arcs but also multiple patterns, zonal/horizontal inhomogeneity, and geomagnetic tilts of SAR arc. Mendillo, Finan, et al (2016) also described a rare kind of SAR arc that includes patches of green line emission induced by low energetic particle precipitation. Ongoing research deals with additional energy source mechanisms for SAR arcs, the influence of ring current evolution upon SAR arcs, and the roles of neutral composition and density.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the SAR arc was caused by the inward movement of the ring current induced by storm-time substorms. Mendillo et al (2016) showed that a SAR arc developed zonally from east to west, and the arc was accompanied by a weak 557.7-nm patchy emission. Shiokawa et al (2009Shiokawa et al ( , 2017 and Takagi et al (2018) reported the detachment of SAR arcs from the auroral oval toward lower latitudes associated with substorm recovery.…”
Section: Introductionmentioning
confidence: 99%